Characteristic of ultra wideband body area network channel - Teawchim, Sanit; Promwong, Sathaporn (My University, 2015)
This paper presents characteristic of ultra wideband body area network (UWB-BAN) channel. The passband rectangular waveform and passband root raised cosine (RRC) waveform are provided to transmit signal. In this paper, an investigation channel measured by using a network analyzer and performed a frequency ranged with 3 GHz–5 GHz. The meander line miniature antennas were taken to obtain as a transmitter and receiver antenna side, repectively. The 12 sample bodies with 10 positions of each body were considered. The linear regression model of large-scale path loss and cumulative distribution function (PDF) of multipath fading factor based on average and peak power loss are shown. Measurement data are useful to predict the performance of UWB-BAN system.
Keywords: Multipath fading; Path loss; Ultra wideband body area network (UWB-BAN)